A educação do campo: uma experiência na formação do (a) educador (a) no estado do Amazonas - Costa, Lucinete Gadelha da (2012)
The research is derived from our experience as teacher in the Superior Normal Course at the University of Amazonas State in the period from 2004 to 2008. It aims, as its general purpose, to understand the guiding principles of the Training Teachers Course for Elementary School in Agrarian Reform Areas in the States of Roraima and Amazonas, in partnership among the University of Amazonas State (UEA), the National Institute for Colonization and Agrarian Reform (INCRA) and the National Program of Education in Agrarian Reform (PRONERA). Regarding the theoretical and methodological procedures of the study we chose the realization of reports in the form of case study, in a qualitative approach through documentary research, semi-structured interviews and analysis of 37 extended abstracts of monographs addressing the issue of teachers training. The Subjects of the research were a representation formed by three students who have already completed the course and four professors of the Discipline of Stage. The systematization of the data conducted from a pre-defined thematic guide allowed the identification of the central ideas of the study that were: the contextualization and principles that underlie the Rural Education; the limits and possibilities of teachers training and the curricular stage as a reference structuring of teacher education. The analysis was guided by the theoretical framework of Popular Education, based in the following authors: Brandão (1984, 1994), Caldart (2000, 2004, 2008, 2009), Fernandes and Molina (2004), Arroyo (1999, 2004, 2010), Bezerra Neto (1999, 2009), Paiva (1973, 1986, 1987), Jesus (2004, 2007), Molina (2004), Haesbaert (2004), Paludo (2001, 2008) and Fernandes (2002, 2004, 2008). Among the main references we have the contribution of Paulo Freire in its specificity in the processes of teacher education. Therefore, it is clear that the process of initiation to research in the perspective of the Rural Education constitutes a reference to the political and pedagogical training of teachers in the State of Amazonas.